2014
DOI: 10.1002/lary.24982
|View full text |Cite
|
Sign up to set email alerts
|

Is human T‐lymphotropic virus type 1 infection associated with hearing loss?

Abstract: HTLV-1 infection, particularly in those with a clinical presentation, appears to accompany hearing loss. Based on the results of PTA and ABR tests, this study may suggest a cochlear source of hearing impairment rather than neural problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This pathway decreases to fifth rank in the treated SSNHL sub‐group. The classic neurological presentation of HTLV‐1 infection is a myelopathy called HTLV‐1 associated myelopathy/tropical spastic paraparesis and individuals infected with this virus have been reported to present with hearing loss . Furthermore, miR‐590‐5p was significantly upregulated in SSNHL patients ( P = .009).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway decreases to fifth rank in the treated SSNHL sub‐group. The classic neurological presentation of HTLV‐1 infection is a myelopathy called HTLV‐1 associated myelopathy/tropical spastic paraparesis and individuals infected with this virus have been reported to present with hearing loss . Furthermore, miR‐590‐5p was significantly upregulated in SSNHL patients ( P = .009).…”
Section: Discussionmentioning
confidence: 99%
“…The combined plantar pressure and stabilometric results indicate that HAM/TSP patients had a significant postural control deficit, which can lead to an increase in risk of falls; that asymptomatic HTLV-1 infected patients are sub-clinically susceptible to these balance impairments; and that they need continuous evaluations of their postural control. Other studies have found functional loss in HTLV-1 patients compared to the control group, such as altered plantar foot pressure 18 , hearing loss 27 , and impaired vestibular evoked myogenic potentials 28 . Nagai et al .…”
Section: Discussionmentioning
confidence: 89%